Effects of pattern coating and vacuum assistance on porosity of aluminium lost foam castings - Guler, Kerem Altug; Kisasoz, Alptekin; Karaaslan, Ahmet (ALLERTON PRESS INC, 2014)
Lost foam casting (LFC) process has several advantages when compared to conventional sand casting techniques however formation of large amount of gaseous products during foam pattern removal increases porosity fraction of castings, especially for low melting point A1 and Mg alloys. In this study pattern coating and vacuum assistance at the time of filling were investigated and their characterizations in constant casting conditions have been determined. Green sand moulding technique was carried out for all moulds because it is necessary to obtain sound castings by using expandable polystyrene (EPS) foam patterns without refractory coating. Simple prismatic shaped patterns were prepared from cutting pieces from an EPS isolation board. A well-known A380 Al-Si-Cu casting alloy was cast at 730A degrees C. As expected, pattern coating reduce the gas permeability and increase porosity however metal penetration into sand grains and surface roughening occurs without coating. Slight vacuum were applied to moulds with vacuum casting machine until solidification. Vacuum assistance enhanced gas removal and it has clear effect on decreasing porosity.
Keywords: Lost foam casting; vacuum assistance; pattern coating; ALLOY; PARAMETERS; Metallurgy & Metallurgical Engineering